Influence of hydrothermal ageing on single lap bonded CFRP joints - Costanzo Bellini; Gianluca Parodo; Wilma Polini; Luca Sorrentino (Fracture and Structural Integrity, 2018)
Nowadays adhesive are widely used in structural applications, in particular for assembly composite materials. In fact, this technique allows to obtain a more uniform load in the joint, to realise a joint with an higher specific strength and to avoid drilling parts as in the case of bolted joints. However, the mechanical properties of bonded parts over time are not well understood if they are subjected to a more or less aggressive environment. Generally, the main factors of influence regarding the durability of bonded joints are humidity and temperature, but their effects are not always clear if these two factors act simultaneously. In this work the effect of hydrothermal ageing on the mechanical resistance of single lap bonded CFRP joints has been investigated. In particular two types of adhesives (AF 163-2K film and EA 9309NA paste) and three ageing environments (thermal cycles from -28 °C to 85 °C in air, distilled water and salt water) have been chosen for the activity.